Pulsed gamma rays from the original millisecond and black widow pulsars: A case for caustic radio emission? - Guillemot, L.; Johnson, T.; Venter, C.; Kerr, M.; Pancrazi, B.; Livingstone, M.; Janssen, G.; Jaroenjittichai, P.; Kramer, M.; Cognard, I.; Stappers, B.; Harding, A.; et al. (Institute of Physics Publishing, 2012)
We report the detection of pulsed gamma-ray emission from the fast millisecond pulsars (MSPs) B1937+21 (also known as J1939+2134) and B1957+20 (J1959+2048) using 18 months of survey data recorded by the Fermi Large Area Telescope and timing solutions based on radio observations conducted at the Westerbork and Nançay radio telescopes. In addition, we analyzed archival Rossi X-ray Timing Explorer and XMM-Newton X-ray data for the two MSPs, confirming the X-ray emission properties of PSRB1937+21 and finding evidence (~4s) for pulsed emission from PSRB1957+20 for the first time. In both cases the gamma-ray emission profile is characterized by two peaks separated by half a rotation and are in close alignment with components observed in radio and X-rays. These two pulsars join PSRsJ0034-0534 and J2214+3000 to form an emerging class of gamma-ray MSPs with phase-aligned peaks in different energy bands. The modeling of the radio and gamma-ray emission profiles suggests co-located emission regions in the outer magnetosphere.